An Efficient certificate Revocation Method For Mobile Ad Hoc Network (International Journal of Engineering and Computer Science, 2014)
Mobile adhoc  networks (MANETs) have attracted  much attention  due to their mobility and ease of deployment. However  the wireless and dynamic natures render them more vulnerable to various types of security attacks than the wired networks. Certificate Revocation is an important integral component to secure network communications. The main challenge for certificate revocation is to revoke the certificates of malicious nodes promptly and accurately. When the certificate of malicious node is revoked,it is denied from all activities and isolated from network. In this paper we build upon previously proposed scheme,a clustering based certificate revocation scheme.This scheme is used for quick revocation  of  attackers certificates and recovery of falsely accused certificates .To overcome the limitation of the Clustering based certificate revocation scheme we use node release method .To identify the malicious nodes the zkp (zero knowledge protocol ) is used.Extensive simulation show that the new method can effectively improve the performance of Certificate Revocation.